Job Satisfaction among Women Teachers in Purba Medinipur District of West Bengal: An Assessment - Maiti, Mr. Dilip (Researchparks Publishing, 2023)
A teacher's optimistic outlook is crucial in the classroom. In order to find fulfillment in their profession, teachers must be able and willing to do their duties with the highest dedication. Feeling emotionally and mentally fulfilled in one's work is what we call